Tactical urbanism or revitalization – a city tailored for the people - Gaweł, Dariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
We live in the conditions of constantly changing cities. Spatial transformations taking place before our eyes concern both older districts, housing estates as well as technical infrastructure or non-urbanized areas. The participation of social organizations and the inhabitants themselves is very important for the success of the entire change process. So far, revitalization has been the most popular process of renewal in Poland. In recent years in many degrading cities of the world, tactical urban projects have proved to be a particularly popular and effective process of transforming public space. This article is an attempt to compare both processes in selected cities, taking into account the benefits of implementing them.